#NoDaysOff: examining the relationship between exercise habits and lifestyle-based consumer behavior - Kim, Minjeong (Frontiers in Psychology, 2025)
This study explores how contemporary lifestyle characteristics shape consumption behaviors. Specifically, it focuses on three key traits: consistent exercise habits reflecting a health-conscious lifestyle, the habitual sharing of daily experiences on social media, and value-driven consumption behaviors aligned with environmental sustainability and fair trade. By examining the main effects, two-way interactions, and a three-way interaction among these variables, the study aims to understand how such lifestyle patterns influence purchase intentions for general consumer goods. A survey of 223 participants was conducted, and regression analysis was used to test the hypotheses. The results reveal that social media engagement significantly predicts purchase intention, and this relationship is moderated by exercise habits—indicating that health-conscious consumers who engage in regular exercise are more influenced by social media. While value-driven consumption did not have a direct effect on purchase intention, it indirectly enhanced purchase intention through its positive interaction with exercise habits. Additional analyses conducted separately for experience goods and search goods showed consistent patterns for search goods; however, the interaction effects were not significant for experience goods. These findings offer insights into the lifestyle-oriented consumer behaviors, emphasizing the role of exercise habits in shaping consumers’ responsiveness to social and value-based influences in the marketplace.